2020
DOI: 10.1098/rspb.2020.1772
|View full text |Cite
|
Sign up to set email alerts
|

Nasal airflow engages central olfactory processing and shapes olfactory percepts

Abstract: Binding of airborne odour molecules to olfactory receptors at the top of the nasal cavity gives rise to our rich olfactory experience. Whether airflow plays a role in human olfactory perception beyond the transportation of odorants is scantly known. Combining psychophysical measures with strict controls of nasal flow parameters, we demonstrate in four experiments that the perceived intensity of a unilaterally presented odour decreases systematically with the amount of contralateral nasal airflow, in manners th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The authors hypothesised that a third variable, inflammation or developmental errors, could explain such a change. Yao et al (2020) provided evidence that the subjective intensity of unilaterally presented odorant decreases with increase of perceived contralateral airflow, independent of sniff vigour and odorant transportation. These findings indicated that the central processing of odorants involves the processing of nasal airflow information, which is relayed from branches of the trigeminal nerve (Yao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors hypothesised that a third variable, inflammation or developmental errors, could explain such a change. Yao et al (2020) provided evidence that the subjective intensity of unilaterally presented odorant decreases with increase of perceived contralateral airflow, independent of sniff vigour and odorant transportation. These findings indicated that the central processing of odorants involves the processing of nasal airflow information, which is relayed from branches of the trigeminal nerve (Yao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al (2020) provided evidence that the subjective intensity of unilaterally presented odorant decreases with increase of perceived contralateral airflow, independent of sniff vigour and odorant transportation. These findings indicated that the central processing of odorants involves the processing of nasal airflow information, which is relayed from branches of the trigeminal nerve (Yao et al, 2020). With regard to the cerebral processing of olfactory information, hemispheres are specialised for various processes, referred to as hemispheric specialisation or brain lateralisation (Rogers, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al indicated that nasal flow spontaneously engages central olfactory processing and is an integral part of the olfactory percept in humans. [ 20 ] Fu et al reported that alteration of nasal airflow affected odor thresholds distinctly. [ 21 ] Lee et al demonstrated an average increment in inspiratory and expiratory airflow resistance of 126% and 122%, respectively, and an average reduction in air exchange of 37% when using the N95 mask.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al (2020) provided evidence that the subjective intensity of unilaterally presented odor decreases with increase of perceived contralateral air ow, independent of sniff vigor and odor transportation. These ndings indicated that the central processing of odors involves the processing of nasal air ow information which is relayed from branches of the trigeminal nerve (Yao et al, 2020). With regard to the cerebral processing of olfactory information, hemispheres are specialized for various processes, referred to as hemispheric specialization or brain lateralization (Rogers, 2021).…”
Section: Discussionmentioning
confidence: 99%